Principles of Security and Trust: 7th International Conference, POST 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Ralf Küsters (Security and Cryptology, 2018)
This book constitutes the proceedings of the 7th International Conference on Principles of Security and Trust, POST 2018, which took place in Thessaloniki, Greece, in April 2018, held as part of the European Joint Conference on Theory and Practice of Software, ETAPS 2018. The 13 papers presented in this volume were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections named: information flow and non-intereference; leakage, information flow, and protocols; smart contracts and privacy; firewalls and attack-defense trees.